Designing Tools that Allows Children in the Early Childhood to Program Robots - Ramírez Benavides, Kryscia Daviana (2017)
This paper describes the design and evaluation process of two mobile programming assistance tools that allow children in the early childhood to develop programs and execute them using robots. The tools are called TITIBOTS and TITIBOTS Colab which incorporates collaboration. The tools have icon-based interfaces and integrate visual programming, robotics, and mobile devices as one tool. The main issues and lessons learned during the design process are described. The methodology used in this project was User-Centered Design (UCD) process. The tools were developed and evaluated applying participatory-design, experience prototyping, and usability testing. The final product are two simple, intuitive, and easy to use tools, for children between 4 and 6 years old. The results were promising: children liked the applications and were willing to continue using it to program robots for solving specific tasks.